Deciphering the Fragmentation of the Human Genome Editing Regulatory Landscape - Mahalatchimy, Aurélie; Rial-Sebbag, Emmanuelle (Frontiers in Political Science, 2022)
Genome editing techniques have generated a growing interest following the discovery of the so-called CRISPR-Cas technique. It has raised a global uproar as regards its use in humans, especially after the 2018 announcement of a Chinese scientist who had used CRISPR to edit the genes of twin embryos. Indeed, one of the greatest concerns, although not the only one, has been the use of genome editing technologies to modify the human germline. In such scientific and technological context, the law plays a key role in framing what should be allowed or prohibited, and under which conditions, to find a balance between safe and accessible innovative treatments and respect of fundamental rights in accordance with the societal values and choices. Within the European Union, several institutions have considered the issues raised by human genome editing, and several legal texts participate in the establishment of the European regulatory framework applicable to human genome editing. Yet we argue in this article that the established regulatory landscape is fragmented in the sense of being divided, split, or segmented. Such fragmentation, which may have been inevitable for historical and technicolegal reasons, produces effects regarding the role of the current regulatory frameworks applicable to human genome editing. Focusing on the European Union and on the French levels of governance, we discuss how such fragmentation takes place through the identification of determinants of the human genome editing fragmented regulatory landscape. We argue that it should be seen as a process providing more contingent responses to human genome editing reflecting changing political and legal contexts.